Studies on Perchlorate Complexes of Cu(II) and Ag(I) with Substituted Benzimidazoles - Donappa, N.; Naikar, S.B. (Asian Journal of Chemistry, 2010)
A series of perchlorate complexes of copper(II) and silver(II) of the compositions CuL2(ClO4)2 L=2-(2´-quinolyl) benzimidazole (2-QylBzIH) 2,2´-bis(benzimidazyl) sulphide (bBzIH2s), 2,2´-bis (benzimidazyl) ethane (bBzIH2e) and AgLClO4 (L=2,6-bis (2-benzimidazyl) pyridine (bBzIH2Py), 2-QylBzIH, BbzIH2s and BbzIH2e have been prepared and characterised by conductivity, magnetic susceptibility, electronic, IR and proton NMR spectra. IR spectra give evidence for coordination of perchlorate in most of these complexes.